2013
DOI: 10.1016/j.resuscitation.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of non-traumatic out-of-hospital cardiac arrest with active compression decompression cardiopulmonary resuscitation plus an impedance threshold device

Abstract: Background A recent out-of-hospital cardiac arrest (OHCA) clinical trial showed improved survival to hospital discharge (HD) with favorable neurologic function for patients with cardiac arrest of cardiac origin treated with active compression decompression cardiopulmonary resuscitation (CPR) plus an impedance threshold device (ACD+ICD) versus standard (S) CPR. The current analysis examined whether treatment with ACD+ITD is more effective than standard (S-CPR) for all cardiac arrests of non-traumatic origin, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 15 publications
(22 reference statements)
0
32
1
1
Order By: Relevance
“…They found a 38% increase in survival to hospital discharge with favorable neurologic outcomes, and a 39% relative increase in one-year survival following cardiac arrest for ACD plus ITD CPR, independent of the cause of cardiac arrest. 24 A 2015 review concluded that compared with standard CPR, ACD plus ITD CPR achieved increased blood flow and associated patient survival rates for out-of-hospital cardiac arrest regardless of etiology. 7 …”
Section: Addition Of the Impedance Threshold Devicementioning
confidence: 99%
See 1 more Smart Citation
“…They found a 38% increase in survival to hospital discharge with favorable neurologic outcomes, and a 39% relative increase in one-year survival following cardiac arrest for ACD plus ITD CPR, independent of the cause of cardiac arrest. 24 A 2015 review concluded that compared with standard CPR, ACD plus ITD CPR achieved increased blood flow and associated patient survival rates for out-of-hospital cardiac arrest regardless of etiology. 7 …”
Section: Addition Of the Impedance Threshold Devicementioning
confidence: 99%
“…21,22,41 One trial comparing conventional CPR and ACD plus ITD CPR found increased one-year survival following cardiac arrest with ACD plus ITD CPR use. 8,24 Due to a lack of research on this method, however, it is not a recommended alternative for conventional CPR unless performed by trained personnel. 29 Mechanical chest compression piston devices are also mentioned in the guidelines.…”
Section: Mechanical Acd Devicesmentioning
confidence: 99%
“…15 The combination of ITD with active compression-decompression CPR may be a reasonable alternative to conventional CPR in settings with available equipment and properly trained personnel. 16,17 Conventional manual chest compressions remain the standard of care for the treatment of cardiac arrest, but mechanical chest compression devices may be a reasonable alternative for use by properly trained personnel. [18][19][20] When rapidly implemented, extracorporeal cardiopulmonary resuscitation (ECPR) can prolong viability for patients who are not resuscitated with conventional CPR.…”
Section: Advanced Life Support-adultmentioning
confidence: 99%
“…2,3 Briefly, the study compared the safety and effectiveness of two methods of cardiopulmonary resuscitation (CPR; active compression decompression CPR plus an impedance threshold device, and standard CPR) administered by emergency medical services (EMS) providers at seven sites across the United States. The primary study endpoint was survival to hospital discharge with favorable neurologic function (Modified Rankin Scale score ≤ 3) in subjects with arrests of presumed cardiac etiologies.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…2,3 Demographic and cardiac arrest characteristics were obtained from EMS run reports and hospital admission data. Outcome data were collected in a variety of ways, depending on the informed consent status of the patient.…”
Section: Study Protocolmentioning
confidence: 99%